2021
DOI: 10.1089/neu.2018.6052
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E4 Polymorphism and Outcomes from Traumatic Brain Injury: A Living Systematic Review and Meta-Analysis

Abstract: The mortality of traumatic brain injury (TBI) has been largely static despite advances in monitoring and imaging techniques. Substantial variance exists in outcome, not fully accounted for by baseline characteristics or injury severity, and genetic factors likely play a role in this variance. The aims of this systematic review were to examine the evidence for a link between the apolipoprotein E4 (APOE4) polymorphism and TBI outcomes and where possible, to quantify the effect size via meta-analysis. We searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 81 publications
(84 reference statements)
1
54
1
Order By: Relevance
“…It follows that the host-response is a key factor in regulating secondary injury processes such as cerebral edema and contusion expansion that significantly influence outcome after TBI. Genetic variation is increasingly recognized as an important contributor to variability in post-traumatic host response [28,[115][116][117][118][119][120][121][122][123][124]. adjacent gene KCNJ11 (encoding KIR6.2).…”
Section: Impact Of Genetic Variation In Abcc8 (Encoding Sur1) and Trpmentioning
confidence: 99%
“…It follows that the host-response is a key factor in regulating secondary injury processes such as cerebral edema and contusion expansion that significantly influence outcome after TBI. Genetic variation is increasingly recognized as an important contributor to variability in post-traumatic host response [28,[115][116][117][118][119][120][121][122][123][124]. adjacent gene KCNJ11 (encoding KIR6.2).…”
Section: Impact Of Genetic Variation In Abcc8 (Encoding Sur1) and Trpmentioning
confidence: 99%
“…Although all of the tauopathies display these tau deposits, the tauopathies are differentiated by the tau isoforms and anatomic distribution. 32 Rare mutations in MAPT cause an autosomal dominant tauopathy (FTDP-17), which may manifest as several clinical phenotypes including frontotemporal dementia COMT, 54,55 ANKK1, 55,56 IL1A, 57 IL1B, 26,58 IL1RN, 59 DRD2, 55,56 TNF, 60 BDNF, [61][62][63] BCL2, 64 mtDNA haplotypes H, J, T, U, 65 mt-ND3, 66 p53, 67 ACE, 68 NGB, 69 ABCB1, 70,103 AQP4, 71 CYP19A1, 72 PARP1, 73 IL6, 74,75 VMAT2 76,77 Genes/loci implicated in poor chronic c outcomes after TBI b APOE4, [78][79][80][81] TMEM106B, 50 BDNF, [61][62][63] mt-ND3, 66 NGB, 69 PPP3CC 105 Genes/loci implicated in AD Early-onset AD: APP, 82 PSEN1, 82 PSEN2, 82 Late-onset AD: CR1, 83,84 INPP5D/SHIP1, 83,84 UNC5C, 85 HBEGF/PFDNI1, 86,87 MEF2C/TMEM161B, 83 TREM2, 88,89 CD2AP/ADGRF2, 83,84 HLA-DRB/HLA-DQB1,…”
Section: Microtubule-associated Protein Taumentioning
confidence: 99%
“…Neurogenesis is affected in an ApoE isoform-dependent manner after both ischemic stroke [39] and controlled cortical impact [17] in mouse models but not after concussion [40]. Recently a large meta-analysis in humans concluded that outcome following TBI occurs in an ApoE isoform-dependent manner thus validating its importance in overall TBI, but the underlying mechanism remains entirely unknown [41].…”
Section: Introductionmentioning
confidence: 99%